The functional quality of decomposing litter outputs from an Arctic plant community is affected by long-term exposure to enhanced UV-B. (January 2016) - Jones, Alan G.; Bussell, Jennifer; Winters, Ana; Scullion, John; Gwynn-Jones, Dylan
Abstract: Plant exposure to enhanced UV-B radiation typically induces changes in leaf secondary metabolite profiles which will be inherited in litter, affecting litter breakdown and the carbon (C) dynamics of sensitive plant communities. A key enzyme in the decomposition process is phenol oxidase which is influenced by litter quality and, hence, a decomposition bioindicator. Here we investigated dwarf shrub litter decomposition following experimental community exposure to enhanced UV-B over two decades in the Swedish sub-Arctic. We examined the hypothesis that foliar UV-B exposure would alter litter quality to elevate phenol oxidase activity. This was tested in the field by measuring phenol oxidase activity in freshly collected mixed-community litter from under our experimental vegetation. A laboratory mesocosm was next used in a decomposition assay to investigate individual species responses over eight weeks, with an emphasis on the quality of leachate outputs from decomposing litter (from Empetrum hermaphroditum, Vaccinium vitis-idaea, Vaccinium uliginosum ). In the assay bi-weekly collections of leachate were analysed for phenol oxidase activity, together with total phenolics and dissolved organic C (DOC). At the end of the assay litter mass loss and respired C were also determined. The initial assessment on field mixed-community litter found no enhanced UV-B treatment (henceforth: 'UV-B treatment') effect on phenol oxidase activity. However, in the controlled laboratory mesocosm assay, significant species-specific effects of the UV-B treatment were evident, with increased phenol oxidase activity in V. vitis-idaea leachate ( P  < 0.001) and a significant reduction ( P  = 0.05) in respired C. Leachate DOC release from the UV-B treatment was greater in both Vaccinium species and the effect on V. uliginosum was significant ( P  < 0.05). The UV-B treatment had no effect on the total phenolic concentration of litter or leachates for any species, but there were significant differences in leachate total phenolics, both over time and between species. Also the initial phenolic concentration in leachates from the decomposing litter of E. hermaphroditum was greater than both Vaccinum species. Results suggest a species specific role for UV-B in influencing enzyme function and decomposition, dependent on individual traits. This has implications for decomposition dynamics in this system and more widely. Our study highlights the value of using a laboratory assay to gain a mechanistic understanding the species level impacts of a global change factor (UV-B) on decomposition, which are otherwise obscured by community-level responses and difficult to determine under field conditions.